Intermediate technology for fish cracker ('keropok') production - Siaw, C. L.; Idrus, A. Z.; Yu, Swee Yean (Wiley-Blackwell, 1985)
'Keropok' production is an important cottage industry in Malaysia. However, production methods used are poor, resulting in inferior quality products which have uneven expansion characteristics, dark objectionable colours and varying shapes, sizes and thicknesses. This paper describes a method that can be used to upgrade 'keropok' production. Basically it is an adaptation from sausage production technology. Products from this method were superior in terms of appearance, shape and linear expansion and were more acceptable to taste panellists.